Exopolysaccharides extracted from Parachlorella kessleri inhibit colon carcinoma growth in mice via stimulation of host antitumor immune responses - Ishiguro, S.; Uppalapati, D.; Goldsmith, Z.; Robertson, D.; Hodge, J.; Holt, H.; Nakashima, A.; Turner, K.; Tamura, Masaaki (My University, 2017)
The newly purified extracellular polysaccharides (exopolysaccharides) from Parachlorella kessleri (PCEPS) were evaluated on their antitumor and immunomodulatory effects in cell culture and mouse colon carcinoma peritoneal dissemination model. In two-dimensional cell culture, the PCEPS treatment inhibited cell growth of both murine and human colon carcinoma cells in a dose- and time-dependent manner. In contrast, the growth of mouse splenocytes (SPLs) and bone marrow cells (BMCs) were stimulated by the treatment with PCEPS. The treatment with PCEPS also increased specific subpopulations of the cells in BMCs: antigen presenting cells (CD19(+) B cells, 33D1(+) dendritic cells and CD68(+) macrophage) and CD8(+) cytotoxic T cells. In three-dimensional spheroid culture, spheroid growth of CT26 cells co-cultured with HL-60 human neutrophilic promyeloblasts and Jurkat cells (human lymphoblasts), but not THP1 human monocyte/macrophage was significantly attenuated by PCEPS treatment. In a mouse CT26 colon carcinoma peritoneal dissemination model, intraperitoneal injection of PCEPS (10 mg/kg, twice per week) significantly attenuated the growth of CT26 colon carcinoma in syngeneic mice. The present study suggests that PCEPS inhibits colon carcinoma growth via direct cell growth inhibition and a stimulation of the host antitumor immune responses. Taken together, the current study suggests that exopolysaccharides derived from Parachlorella kessleri contain significant bioactive materials that inhibit colon carcinoma growth.
Citation: Ishiguro, S., Uppalapati, D., Goldsmith, Z., Robertson, D., Hodge, J., Holt, H., . . . Tamura, M. (2017). Exopolysaccharides extracted from Parachlorella kessleri inhibit colon carcinoma growth in mice via stimulation of host antitumor immune responses. Plos One, 12(4), 21. https://doi.org/10.1371/journal.pone.0175064
Keywords: Unicellular Green-Algae; Tumor-Bearing Mice; Chlorella-Vulgaris; Attenuates Growth; Cell-Lines; Polysaccharides